Targeting steroid hormone receptors for anti‐cancer therapy—A review on small molecules and nanotherapeutic approaches. (19th September 2021) - Mahadik, Namita; Bhattacharya, Dwaipayan; Padmanabhan, Akshaya; Sakhare, Kalyani; Narayan, Kumar Pranav; Banerjee, Rajkumar
Abstract: The steroid hormone receptors (SHRs) among nuclear hormone receptors (NHRs) are steroid ligand‐dependent transcription factors that play important roles in the regulation of transcription of genes promoted via hormone responsive elements in our genome. Aberrant expression patterns and context‐specific regulation of these receptors in cancer, have been routinely reported by multiple research groups. These gave an window of opportunity to target those receptors in the context of developing novel, targeted anticancer therapeutics. Besides the development of a plethora of SHR‐targeting synthetic ligands and the availability of their natural, hormonal ligands, development of many SHR‐targeted, anticancer nano‐delivery systems and theranostics, especially based on small molecules, have been reported. It is intriguing to realize that these cytoplasmic receptors have become a hot target for cancer selective delivery. This is in spite of the fact that these receptors do not fall in the category of conventional, targetable cell surface bound or transmembrane receptors that enjoy over‐expression status. Glucocorticoid receptor (GR) is one such exciting SHR that in spite of it being expressed ubiquitously in all cells, we discovered it to behave differently in cancer cells, thus making it a truly druggable target for treating cancer. This review selectively accumulates the knowledge generated in the field of SHR‐targeting as a major focus for cancer treatment with various anticancer small molecules and nanotherapeutics on progesterone receptor, mineralocorticoid receptor, and androgen receptor while selectively emphasizing on GR and estrogen receptor. This review also briefly highlights lipid‐modification strategy to convert ligands into SHR‐targeted cancer nanotherapeutics. This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Oncologic Disease Biology‐Inspired Nanomaterials > Lipid‐Based Structures Therapeutic Approaches and Drug Discovery > Emerging Technologies Abstract : Targeting steroid hormone receptors for anticancer therapy.